Redefining culture : perspectives across the disciplines - Baldwin, John R., 1960- (LEA's communication series., 2006)
Argues that culture is perhaps the most important thing to know about people if one wants to make predictions about their behavior. The goal of this volume is to present a theoretically exhaustive integration of multidisciplinary approaches.